Perkembangan Bahasa Pada Anak Usia Dini - Heny Friantary (Zuriah : Jurnal Pendidikan Anak Usia Dini, 2020)
Language development in early childhood is the most important aspect for early childhood. Through language, children can develop the ability to communicate with other people and children can express their thoughts using language so that other people can understand what the child is thinking. On the other hand, it is not surprising that language is considered as an indicator of a child's success. In the aspect of language development, the expected competence and results are that children are able to use language as a passive understanding of language and can communicate effectively which is useful for thinking and learning well. The role of parents is very important for children's language development by providing appropriate stimulations so that language development can develop optimally